2009
DOI: 10.1111/j.1600-0404.2009.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dementia and cognitive impairment in Southeastern Spain: the Ariadna study

Abstract: The prevalence of dementia was low, despite a high prevalence of aMCI and CIND. Dementia was strongly associated with age and education. CIND was associated with living in a rural area and with female sex, while aMCI was associated with illiteracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
41
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 42 publications
15
41
4
1
Order By: Relevance
“…Only few studies have reported that male gender is associated with a higher MCI risk [42,52] . Most studies confirm our findings for the original MCI definition with no difference in gender or report a higher prevalence rate for women [38,39] . A possible explanation could be the limited insight especially of older participants and men into cognitive impairments as part of the MCI-original diagnosis.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Only few studies have reported that male gender is associated with a higher MCI risk [42,52] . Most studies confirm our findings for the original MCI definition with no difference in gender or report a higher prevalence rate for women [38,39] . A possible explanation could be the limited insight especially of older participants and men into cognitive impairments as part of the MCI-original diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…According to the MCI-modified criteria, a higher prevalence rate was found (12.1%), which also falls within the reported range of 5-42% of other population-based studies [34,[37][38][39] . This is also consistent with the finding that the modified diagnoses are more common than the original [34] , which may be due to the fact that requiring one criterion less increases the sensitivity but reduces the specificity of the MCI concept.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The superior schooling of Chilean women, as well as their prolonged interactions with family members, might stimulate cognitive function (28,29) . As in other studies, a lower risk of cognitive impairment was observed in those with higher levels of education (30)(31)(32) , which might be explained by greater cognitive reserves from superior cortical and neuronal synaptic capacities or improved compensation for deficiencies arising from other brain regions (33,34) . Although the difference in SF levels was statistically significant when comparing our participants with normal and impaired cognitive function (MMMSE plus PFAQ), it should be noted that in both cases SF levels were within the normal range, reaching supraphysiological levels (>20 μg/l) (35) in the group with normal cognitive function.…”
Section: Discussionsupporting
confidence: 53%
“…Large differences are found between the prevalence of CIND among rural and urban populations. Two studies in Spain reported CIND prevalence rates of 13.8 and 14.7% in an urban setting [16,17] compared to 23.3% found in a rural setting [17]. Similarly, in a study of the Beijing population, Tang et al [18] reported that CIND was higher in rural locations compared to urban locations (18.8 vs. 6.9%, respectively).…”
Section: Discussionmentioning
confidence: 94%